On the Viability of an International Lender of Last Resort - Zanker, Benedikt, MSc (Nomos Verlagsgesellschaft mbH & Co. KG, 2007)
Over the last decade the global financial system has been shaken by financial crises in emerging economies all over the world. The result of these crises has been turmoil in financial markets, a severe deceleration of economic growth and hardship in the economies involved. The International Monetary Fund was quickly identified as a main culprit and has been the subject of intense debate ever since. While a consensus has developed that the Fund is in need of wide-ranging reforms, an agreement on which reform path to follow is still lacking. An often recurring proposal is to restructure the IMF into an international lender of last resort along the lines developed by Walter Bagehot, then editor of the Economist, in the late 19th century. Although this proposal appears initially suggestive, it has been frequently dismissed out of hand as unrealistic by policy makers as well as academics. The book analyses in detail whether this dismissal is founded or whether a rigourous reform along Bagehotian lines could indeed help to increase the stability of the global financial system.